Northern Ways to Think About Music: Glenn Gould's Idea of North as an Aesthetic Category - Mantere, Markus (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2005)
This article discusses the role played by the concept of "North" in Glenn Gould's musical thought. In Gould's writings and interviews, the meaning of the "North" is twofold: ( 1) The concept refers to musical phenomena and qualities (counterpoint, non-virtuosity, sonic austerity) which were important for Gould's value judgments of music; (2) Gould used the concept as a metaphor, enabling him to bring together the ideas of isolation, the use of technology to creatively "opt-out," and the notion of non-competition into a coherent aesthetic and ethical perspective. Through a study of Gould's written documents, the concept of "North" will be examined to establish a hermeneutic framework within which to better appreciate and evaluate Gould's musicianship.